Complete Genome Sequence of Serratia marcescens Siphophage Slocum - Snowden, Jason (Microbiol Resour Announc, 2020)
Serratia marcescens is a ubiquitous Gram-negative opportunistic pathogen. This announcement describes the isolation and genome annotation of S. marcescens T5-like siphophage Slocum. Terminal repeats, 170 protein-coding genes, and 23 tRNAs were predicted in the 112,436-bp Slocum genome.